Effect of temperature and light on the stability of fat-soluble vitamins in whole blood over several days: implications for epidemiological studies. - Clark, S; Youngman, L; Chukwurah, B; Palmer, A; Parish, S; Peto, R; Collins, R (2004)
BACKGROUND: Biochemical measurement of fat-soluble vitamins would allow direct assessment in epidemiological studies of their association with disease. However, the perceived instability of these compounds and typically high cost of collection and analysis may make their measurement impractical, particularly in large-scale studies. Using a high performance liquid chromatography assay developed in-house, we have investigated the separate effects of temperature and light on the stability of vitamins in whole blood over several days. METHODS: Multiple blood samples from 10 volunteers were stored at 20 degrees C or 4 degrees C and in dark or light conditions. Immediately after collection and 1, 2, 3, 4, and 7 days later, samples stored under each condition were centrifuged, and the plasma was aliquoted and stored at -80 degrees C. Subsequently, all aliquots from each individual were analysed in one analytical run. RESULTS: In whole blood stored under any of the four conditions for up to 7 days, concentrations of alpha-carotene, beta-carotene, lutein, lycopene, retinol, and alpha-tocopherol changed by less than 8%, and cryptoxanthin and gamma-tocopherol by less than 11%. Although significant temperature effects were observed for alpha-carotene, and alpha- and gamma-tocopherol, and a significant effect of light was observed for alpha-carotene, cryptoxanthin, and lycopene, these analytes changed by less than 1% per day under all conditions. CONCLUSIONS: Concentrations of these fat-soluble vitamins change by only a few per cent in whole blood during storage at room temperature for several days. Hence, delayed separation of blood samples (which may be required for practical reasons in large-scale epidemiological studies) does not preclude reliable measurement of fat-soluble vitamins.